Transport planning with accessibility indices in the Netherlands - Karst T. Geurs (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This discussion paper overviews the different perspectives and approaches to measuring accessibility, reviews the strengths and weaknesses of different accessibility indicators and describes the use of accessibility indicators in the Dutch policy and planning practice. In choosing accessibility measures, there clearly is a trade-off between theoretical and practical strengths/weaknesses. Dutch transport planners have focused on infrastructure-based accessibility metrics. Only in recent years, increasing attention has been paid to integrated transport, spatial planning and more advanced accessibility measurements. A growing stream of studies explores the concept of accessibility in order to examine equity and distributive justice of transport policies. The choice and operationalisation of accessibility indicators for equity and distributive justice is currently still open for discussion. It requires a more complete understanding of accessibility than traditional indicators offer, and also depends on the theory of justice used.
Keywords: 330